THROUGH THICK AND THIN: FROM THE REGULATION OF QUEERNESS TO QUEER THEORY AS DECOLONISATION (The Pretoria Student Law Review, 2021)
The purpose of this essay is to investigate, criticise and recontextualise the concept of queerness in South Africa. I will do this by focusing on the historical regulation of queerness, the attempted transformation of queerness and the inevitable decolonisation of queerness. This critical investigation and analysis will be centred around three main questions regarding queerness: (1) How queerness has been regulated by western and apartheid concepts of social interaction?; (2) How queerness has been transformed in Post-1994 South Africa — specifically before and after the implementation of the Civil Union Act?; and (3) How can the current marriage systems — and queerness — be decolonised using queer theory? I will approach this essay using concepts of transformative constitutionalism, queer theory, and decolonial theory. By answering these three questions, I aim to prove that queerness (as a concept and identity) is something that requires sufficient decolonisation because it has been historically regulated, inaccurately defined and inadequately transformed. Furthermore, I will demonstrate how legal systems and knowledge, dealing with queerness, ought to be interrogated and altered to best represent queer people.
Keywords: South Africa; queerness; transformation of queerness; decolonisation of queerness; queer theory; transformative constitutionalism